Effects of Near-Fault Pulse-Like Ground Motion on Seismic Response of Dry Sand Site - LIU Hongshuai; SONG Dongsong; DONG Xinyi; WANG Tiqiang (工程科学与技术)
ObjectiveNear-fault pulse-like ground motions (NFPLGMs) exhibit significantly higher destructive potential on structures and site liquefaction compared to non-pulse motions. However, their influence on the seismic response of dry sand sites remains inadequately characterized. Furthermore, a systematic understanding of the differential impacts between near-field and far-field ground motions (FFGMs) on site-specific ground motion parameters is lacking. This study addresses this critical research gap by investigating the specific effects of NFPLGMs on dry sand sites, providing essential theoretical support for the seismic design of engineering structures, particularly long-period structures, thereby enhancing design safety and rationality.MethodsCentrifuge shaking table tests were conducted on dry sand site models using the DCIME-40-300 large dynamic centrifuge at the Institute of Engineering Mechanics, China Earthquake Administration. Fujian standard sand constituted the model, with a total thickness of 58.8 cm. At a centrifugal acceleration of 50g, this corresponded to a prototype height of 29.4 m. Instrumentation included twelve horizontal accelerometers and one surface settlement displacement sensor. Variable-amplitude sine loads from the LEAP project, scaled to different peak accelerations (PGAs), served as the table input. A 1D site seismic analysis model was established using the DEEPSOIL platform. Model calibration focused on optimally matching the experimental peak acceleration profile and surface acceleration response spectrum. The shear wave velocity profile was determined through comparative evaluation of three models (Liu Hongshuai et al., Gu et al., Wang and Stokoe), selecting the Wang and Stokoe model. Similarly, soil nonlinearity was modeled by comparing the Darendeli, Menq, Roblee and Chiou models, with the Darendeli model selected. The seismic inputs comprised 20 NFPLGMs, 20 near-fault non-pulse ground motions (NFNPGMs), and 20 FFGMs, scaled to various PGAs. Their effects on dry sand site response parameters were systematically analyzed, with FFGMs serving as the benchmark for quantitative comparison.Results and Discussions The study showed that the site PGA induced by NFPLGMs was only 6% higher than by FFGMs. In the long-period range (>3.0 s), the site surface SA under NFPLGMs exceeded that under FFGMs by 350-450%, significantly surpassing current code limits. Short-period SA (0.01～0.10 s) was similar for all motion types. Medium-period SA (0.1～1.0 s) under FFGMs was significantly higher than under NFNPGMs, which was slightly higher than under NFPLGMs. Long-period SA (1-10 s) under NFPLGMs was markedly higher than under FFGMs or NFNPGMs. The PGA amplification factor generally decreased with increasing input PGA. For input PGA<0.4g, amplification increased towards the surface (factor >1). For input PGA ≥ 0.4g, amplification decreased initially then increased towards the surface, but remained <1, indicating soil attenuation. The depth-wise variation pattern of amplification was consistent for NFPLGMs, NFNPGMs, and FFGMs, with minor magnitude differences. The maximum Shear Strain (γmax) increased sharply with depth and input PGA under NFPLGMs. The difference in γmax between NFPLGMs and FFGMs increased from 20% at 0.1g input PGA to 420% at 0.8g input PGA. Under the same input PGA, γmax within the soil profile initially increased then decreased towards the surface. NFPLGMs significantly increased γmax compared to NFNPGMs and FFGMs, which yielded similar strains. The depth of maximum γmax under NFPLGMs was deeper than under other motions. Site peak ground displacement (PGD) decreased with depth but increased significantly with input PGA. The difference in PGD between NFPLGMs and FFGMs increased from 20% at 0.1g input PGA to 550% at 0.8g input PGA. PGD increased towards the surface for all motions. NFPLGMs significantly increased PGD compared to FFGMs, while NFNPGMs slightly reduced it. The largest PGD difference occurred near the surface. Analysis against China's GB/T 50011—2010 (2024 edition) revealed that current near-fault amplification factors (1.5 within 5km, ≥1.25 within 10km of faults) overestimate seismic demand for structures with natural periods (T) < 1.0 s, moderately underestimate demand for T = 1.0~3.0s, and severely underestimate demand for T> 3.ConclusionsThe calibrated numerical model, utilizing the Wang and Stokoe shear wave velocity profile and Darendeli nonlinear constitutive model within DEEPSOIL, effectively replicated centrifuge test results, validating its reliability. The near-fault pulse effect exerts a dominant control on long-period acceleration response (T> 3.0s), deep soil shear strain, and large displacement evolution, while its impact on PGA is marginal. For long-period flexible structures (T> 3.0s), design ground motion parameters should be increased to 4.5~5.5 times the standard code values. These conclusions are derived for homogeneous dry sand sites under 1D conditions; validation for complex sites and 2D/3D simulations is recommended. This study elucidates the influence of NFPLGMs on dry sand sites, providing critical insights for performance-based seismic design and code improvement.